A study on drama therapy to promote imagination development of autistic children--A case study in Guangxi, China - Lin Kechen; Sim, Chee Cheang; Sharifuddin Zainal (Scopus, 2024)
Autism spectrum disorder (ASD) provides a neuro-developmental condition disorder that has been characterized by difficulties in social interaction, communication, along with imagination. Children's imagination, a vital aspect of cognitive development, enables them to participate in social role-play, problem solving, and creative thinking. However, imaginative play is frequently difficult for autistic children, which restricts their capacity to express creativity and explore hypothetical situations. This restriction can influence their emotional intelligence and social development, which are normally enhanced by imaginative play. The goal of the case study in Guangxi, China, is to analyze the use of drama therapy to encourage the development of autistic children's imaginations. A sample of 32 individua ls aged 4-7 years old, consisting of 21 males and 11 females, participated in an 8-week experiment. The experiment involved drama therapy sessions held twice a week, with each session lasting for 30 minutes. Notably, none of the participants had prior experience with drama therapy. Pre- and post-intervention data were gathered to evaluate enhancements in emotional expressiveness, social interaction, and imagination. Feedback from parents and teachers was also collected to assess behavioral modifications in natural environments. The data was analyzed using statistical approaches, such as descriptive statistics and ttests. The results demonstrated significant improvements in imagination and creative thinking, along with positive changes in social interaction and communication. Despite some logistical issues, participants, parents, and teachers were quite pleased with the program. The findings indicate that drama therapy is a potential strategy for supporting imaginative development in autistic children, warranting additional research in greater, controlled investigations.